Parent–Child Communication and Adjustment Among Children With Advanced and Non-Advanced Cancer in the First Year Following Diagnosis or Relapse. (27th March 2017) - Keim, Madelaine C.; Lehmann, Vicky; Shultz, Emily L.; Winning, Adrien M.; Rausch, Joseph R.; Barrera, Maru; Jo Gilmer, Mary; Murphy, Lexa K.; Vannatta, Kathryn A.; Compas, Bruce E.; Gerhardt, Cynthia A.
Abstract: Objectives: To examine parent–child communication (i.e., openness, problems) and child adjustment among youth with advanced or non-advanced cancer and comparison children. Methods: Families ( n = 125) were recruited after a child's diagnosis/relapse and stratified by advanced ( n = 55) or non-advanced ( n = 70) disease. Comparison children ( n = 60) were recruited from local schools. Children (ages 10–17) reported on communication (Parent–Adolescent Communication Scale) with both parents, while mothers reported on child adjustment (Child Behavior Checklist) at enrollment (T1) and one year (T2). Results: Openness/problems in communication did not differ across groups at T1, but problems with fathers were higher among children with non-advanced cancer versus comparisons at T2. Openness declined for all fathers, while changes in problems varied by group for both parents. T1 communication predicted later adjustment only for children with advanced cancer. Conclusions: Communication plays an important role, particularly for children with advanced cancer. Additional research with families affected by life-limiting conditions is needed.